KECERDASAN INTELEKTUAL, KECERDASAN EMOSIONAL, DAN KECERDASAN SPIRITUAL BERPENGARUH TERHADAP PEMAHAMAN AKUNTANSI PADA MAHASISWA - Supra, Deswati (Fakultas Ekonomi Universitas IBA, 2017)
The aims of this study is to determine the influence of Intellectual Intelligence,Emotional Intelligence, and Spiritual Intelligence toward Accounting Understanding ofAccounting Under Graduate Students at STIE Rahmaniyah Sekayu. Theoretical basiswere used in this study are intellectual intelligence, emotional intelligence, spiritualintelligence, and understanding of accounting. Independent variables in this study wereintellectual intelligence, emotional intelligence, and spiritual intelligence. While thedependent variable was the understanding of accounting. The population in this studywas all students of S1 Accounting in academic year 2013/2014 with the total numberwas 186 people. The sample in this study was 127 respondents.Technique for collecting the data in this study were done by interview andquestionnaires. This research used multiple regression analysis with data processing toolusing SPSS version 20 program. This research found Intellectual Intelligence, EmotionalIntelligence, and Spiritual Intelligence significantly and positively influence to theUnderstanding of Accounting to the under graduate students of Accounting at STIERahmaniyah Sekayu.